인천지역 성인의 식생활 라이프스타일에 따른 가당음료 소비실태와 혈중지질 - 김송희(Kim, Song Hee); 박소현(Park, So Hyun); 장경자(Chang, Kyung Ja) (Journal of nutrition and health, 2017)
Purpose: The purpose of this study was to investigate the consumption behaviors of sugar-sweetened beverages and blood lipid profiles according to food-related lifestyles of adults in Incheon. Methods: Subjects were recruited from 19 to 64 year old adults residing in Incheon who visited for the purpose of a health examination at D hospital. A total of 110 subjects consented to participate in this study and to allow their health examination records to be used at D hospital. Data were collected using self-administered questionnaires and anthropometric data, and blood lipid profiles were collected from health examination records. Statistical analysis was performed using the SPSS 20.0 program. Results: In the factor analysis, food-related lifestyles were categorized into four factors: planned purchase seeking, taste seeking, well-being seeking, and convenience seeking. Using the K-average clustering method, food-related lifestyles of subjects were categorized into two groups: health and rationality-oriented group (HRG) and convenience purchase-oriented group (CPG). Average total scores of sugar-related nutrition knowledge in the HRG were significantly higher compared to the CPG, and average scores of consumption habits regarding sugar-containing foods in the HRG were significantly lower compared to the HRG. When subjects chose sugar-sweetened beverages, the CPG showed a significantly higher frequency of checking food labeling and considering nutrition compared to the CPG. Drinking frequency of carbonated beverages in the CPG was significantly higher compared to the HRG. Conclusion: There were significant differences in sugar-related nutrition knowledge and consumption habits of sugar-sweetened beverages between the two food-related lifestyle groups. These results could be useful for establishing guidelines for reducing consumption of sugar-sweetened beverages. In addition, it is necessary to continue sugar-related nutrition education by considering the food-related lifestyles of adults. 본 연구는 인천지역에 위치한 D병원에 건강검진을 목적으로 방문한 인천지역 거주자 성인 107명을 대상으로 식생활 라이프스타일, 당 관련 영양지식, 가당식품 소비습관, 가당음료 소비행동 및 섭취빈도를 알아보고, 식생활 라이프스타일 추구성향에 따른 당 관련 영양지식, 가당식품 소비습관, 신체계측치와 혈중지질 농도간의 상관관계를 통한 당 섭취 저감화와 건강한 가당음료 소비행동 개선을 위한 기초자료 제공을 목적으로 하였다. 식생활 라이프스타일 추구성향은 요인분석 결과에 따라 계획구매성향, 맛추구성향, 웰빙추구성향, 간편추구성향의 4개 요인으로 추출되었다. 식생활 라이프스타일 추구성향에 따라 군집분석을 통하여 2개의 집단으로 정하여 건강 합리지향 그룹과 편의구매지향 그룹으로 분류하였다. 식생활 라이프스타일 추구성향에 따른 두 군집간의 비만평가와 혈중 지질 농도는 유의한 관련 및 차이가 없었다. 식생활 라이프스타일 추구성향에 따른 두 군집의 당 관련 영양지식 수준은 건강 합리지향 그룹이 편의구매지향 그룹보다 유의적으로 높게 나타났으며, 10문항 중 무가당 주스에는 당이 없다는 항목에서 지식수준의 차이가 나타났다. 가당식품을 선호하는 소비습관은 편의구매지향 그룹이 건강 합리지향 그룹보다 유의하게 높았으며, 생과일보다 생과일 주스를 자주 마신다는 항목을 제외하고, 모든 문항에 대하여 편의구매지향 그룹이 가당식품에 대한 높은 소비습관을 보였다. 가당음료에 대한 소비행동을 조사한 결과, 건강 합리지향 그룹은 편의구매지향 그룹보다 가당음료 선택 시 식품 표시사항 확인여부와 영양적인 면을 고려하여 구매하는 것으로 나타났다. 그리고 가당음료 중 탄산음료의 소비는 편의구매지향 그룹이 건강 합리지향 그룹보다 소비하는 빈도가 유의하게 높았다. 본 연구의 결과, 가당음료 저감화를 위한 합리적이고 건강한 식생활 라이프스타일로 개선함이 당 섭취를 낮추는데 효과적일 것으로 사료된다.